Ethnomedicinal plants used for malaria treatment in Rukungiri District, Western Uganda - Gumisiriza, Hannington; Olet, Eunice Apio; Mukasa, Paul; Lejju, Julius Bunny; Omara, Timothy (Tropical Medicine and Health, 2023)
Background: Malaria remains a major global health challenge and a serious cause of morbidity and mortality in sub- Saharan Africa. In Uganda, limited access to medical facilities has perpetuated the reliance of indigenous communities on herbal medicine for the prevention and management of malaria. This study was undertaken to document ethnobotanical knowledge on medicinal plants prescribed for managing malaria in Rukungiri District, a meso-endemic malaria region of Western Uganda. Methods: An ethnobotanical survey was carried out between May 2022 and December 2022 in Bwambara Sub- County, Rukungiri District, Western Uganda using semi-structured questionnaire. A total of 125 respondents (81 females and 44 males) were randomly selected and seven (7) key informants were engaged in open interviews. In all cases, awareness of herbalists on malaria, treatment-seeking behaviour and herbal treatment practices were obtained. The ethnobotanical data were analyzed using descriptive statistics, informant consensus factor and preference ranking. Results: The study identified 48 medicinal plants belonging to 47 genera and 23 families used in the treatment of malaria and its symptoms in the study area. The most frequently cited species were Vernonia amygdalina, Aloe vera and Azadirachta indica. Leaves (74%) was the most used plant organ, mostly for preparation of decoctions (41.8%) and infusions (23.6%) which are administered orally (89.6%) or used for bathing (10.4%). Conclusions: Indigenous knowledge of medicinal plants used as prophylaxis and for treatment of malaria still exist among the local communities of Bwambara Sub-County. However, there is a need to investigate the antimalarial efficacy, phytochemical composition and safety of species (such as Digitaria abyssinica and Berkheya barbata) with high percentage use values to validate their use.
Keywords: African traditional medicine; Antimalarial resistance; Ethnobotanical knowledge; Malaria; Medicinal plants